Development of Qur'an Hadith Module Based on Contextual Approach to Improve Students' Critical Thinking Skills at MAN 5 Hulu Sungai Tengah - Khairun Nisa; Akhmad Rahim Mubtadi (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to develop a contextual approach-based Al-Qur'an Hadith module with the theme "Religious Tolerance" to improve critical thinking of class XI students of MAN 5 Hulu Sungai Tengah. This module is designed so that students can understand the concept of religious tolerance through an approach that is relevant to their daily lives. The research method used is research and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Research data were collected through critical thinking tests, observations, questionnaires, and interviews. The results of the study indicate that the developed module is effective in improving students' critical thinking. This can be seen from the increase in students' average scores in critical thinking tests before and after using the module. In addition, students showed an increase in their ability to analyze, evaluate, and make logical conclusions related to the concept of religious tolerance from the perspective of the Al-Qur'an and Hadith. These findings indicate that a contextual approach-based module can be one solution in improving students' understanding of Islamic values ​​that are applicable in their lives.